Quality of bowel cleansing in hospitalized patients undergoing colonoscopy: A multicentre prospective regional study. Issue 8 (August 2015) - Rotondano, Gianluca; Rispo, Antonio; Bottiglieri, Maria E.; De Luca, Leonardo; Lamanda, Roberto; Orsini, Luigi; Bruzzese, Dario; Galloro, Giuseppe; Romano, Marco; Miranda, Agnese; Loguercio, Carmelina; Esposito, Pasquale; et al.
Abstract Background Quality of bowel cleansing in hospitalized patients undergoing colonoscopy is often unsatisfactory. No study has investigated the inpatient or outpatient setting as cause of inadequate cleansing. Aims To assess degree of bowel cleansing in inpatients and outpatients and to identify possible predictors of poor bowel preparation in the two populations. Methods Prospective multicentre study on consecutive colonoscopies in 25 regional endoscopy units. Univariate and multivariate analysis with odds ratio estimation were performed. Results Data from 3276 colonoscopies were analyzed (2178 outpatients, 1098 inpatients). Incomplete colonoscopy due to inadequate cleansing was recorded in 369 patients (11.2%). There was no significant difference in bowel cleansing rates between in- and outpatients in both colonic segments. In the overall population, independent predictors of inadequate cleansing both at the level of right and left colon were: male gender (odds ratio, 1.20 [1.02–1.43] and 1.27 [1.05–1.53]), diabetes mellitus (odds ratio, 2.35 [1.68–3.29] and 2.12 [1.47–3.05]), chronic constipation (odds ratio, 1.60 [1.30–1.97] and 1.55 [1.23–1.94]), incomplete purge intake (odds ratio, 2.36 [1.90–2.94] and 2.11 [1.68–2.65]) and a runway time >12 h (odds ratio, 3.36 [2.40–4.72] and 2.53 [1.74–3.67]). Conclusions We found no difference in the rate of inadequate bowel preparation between hospitalized patients and outpatients.